Efeito do gasto público social sobre indicadores de pobreza e extrema pobreza em nível estadual - Tôrres, José Maria Cipriano (2019)
Between 2003 and 2014, it was possible to see a significant advance in terms of falling indicators of poverty and income inequality in Brazil. However, information published by the Brazilian Institute of Geography and Statistics showed that the downward trend in poverty suffered a reversal from 2015, reflecting the onset of the recession that would significantly affect the Brazilian economy in subsequent years. At the same time, data from the National Treasury Secretariat pointed to a significant growth in direct social spending, with an increase close to 3 percentage points of GDP when compared to the 2002 and 2015 levels. It should be noted that the fiscal situation at the federal, state and municipal levels has deteriorated substantially after 2015, also due to the economic recession. Given this scenario and current budget constraints, it is necessary to map the effectiveness of public spending, especially social spending, and to measure its real impact on reducing poverty rates. This paper, motivated by this context, aimed to assess the impact of social spending, whether aggregate or discriminated by budget functions - social security and care, health and sanitation, education and culture, working, housing and urbanism and investment (in the case of states) - in reducing poverty and extreme poverty rates. Using state-level data for the period from 1995 to 2015, the panel data econometric methodology was adopted to estimate the effect of federal and state spending on poverty and on extreme poverty indicators. Among the results obtained in the study, the most relevant was the finding that state social spending was not statistically significant for the reduction of poverty and extreme poverty in the period from 1995 to 2015. In relation to federal social spending, had an effect. significant with negative coefficient the following functions: social security and care, work and housing and urbanism. However, federal education and culture spending had a significant effect, but with a positive coefficient, thus showing a regressive effect on poverty and extreme poverty rates. This study is very relevant since the current economic debate points precisely to the necessary reduction of public spending and, at the same time, greater effectiveness in combating poverty and inequality.